Effect of exercise on apparent total tract digestibility of nutrients and faecal recovery of ADL and TiO2 in ponies. (7th March 2018) - Schaafstra, F. J. W. C.; van Doorn, D. A.; Schonewille, J. T.; Roelfsema, E.; Westermann, C. M.; Dansen, O.; Jacobs, M.; Lee, J.-Y.; Spronck, E. A.; Blok, M. C.; Hendriks, W. H.
Abstract : Exercise and physical training are known to affect gastrointestinal function and digestibility in horses and can lead to inaccurate estimates of nutrient and energy digestibility when markers are used. The effect of exercise on apparent nutrient digestibility and faecal recoveries of ADL and TiO2 was studied in six Welsh pony geldings subjected to either a low- (LI) or high-intensity (HI) exercise regime according to a cross-over design. Ponies performing LI exercise were walked once per day for 45 min in a horse walker (5 km/h) for 47 consecutive days. Ponies submitted to HI exercise were gradually trained for the same 47 days according a standardized protocol. Throughout the experiment, the ponies received a fixed level of feed and the daily rations consisted of 4.7 kg DM of grass hay and 0.95 kg DM of concentrate. The diet was supplemented with minerals, vitamins and TiO2 (3.0 g Ti/day). Total tract digestibility of DM, organic matter (OM), CP, crude fat, NDF, ADF, starch, sugar and energy was determined with the total faeces collection (TFC) method. In addition, DM and OM digestibility was estimated using internal ADL and the externally supplemented Ti as markers. Urine was collected on the final 2 days of each experimental period. Exercise did not affect apparent digestibility of CP, crude fat, starch and sugar. Digestibility of DM (DMD), OM (OMD), ADF and NDF tended to be lower and DE was decreased when ponies received the HI exercise regime. For all treatments combined, mean faecal recoveries of ADL and Ti were 87.8±1.7% and 99.3±1.7%, respectively. Ti was not detected in the urine, indicating that intestinal integrity was maintained with exercise. Dry matter digestibility estimated with the TFC, ADL and Ti for ponies subjected to LI exercise were 66.3%, 60.3% and 64.8%, respectively, while DMD for HI ponies were 64.2%, 60.3% and 65.2%, respectively. In conclusion, physical exercise has an influence on the GE digestibility of the feed in ponies provided with equivalent levels of feed intake. In addition, the two markers used for estimating apparent DMD and OMD indicate that externally supplemented Ti is a suitable marker to determine digestibility of nutrients in horses performing exercise unlike dietary ADL.